Energy options from the 20th Century: Comparing Conventional and Nuclear Energy from a Sustainable Standpoint - Ndeh Mboumien Ngang, Eric (JNRD - Journal of Natural Resources and Development, 2012)
Different Energy options have been the driving force for the world economy with an evolution in types and sources. Decades ago choosing what energy option to use did not call for much debate as issues of sustainability, pressure on our environment, and our climate were not a major concern. However today, humans have to grapple with these current global challenges especially those exacerbated by our current sources of energy. The review article argues that science and sustainability thinking should be the basis for making the choice about what energy option is suitable for our era. It proposes that a more fruitful discourse should follow from a dialogue that puts in place the set of sustainability indicators and evaluating the suitability of the options for our era in that context. Focusing on two energy options; conventional and nuclear energy; the review compares them based on a set of sustainability indicators including, but not limited to, the environment, economics, ethics, expertise requirements, technical information, health, safety, uncertainty and government funding. In trying to answer the question Unsustainable conventional energy sources, is nuclear energy similar?, the review concludes that despite the demerits of nuclear energy, it is the solution to meet the world’s growing energy needs and to reverse the impending threat posed by climate change if research and development efforts in the sector are accelerated.
Keywords: Conventional energy; Nuclear energy; Sustainability